A novel combined approach for compositional and Pb isotope data of (leaded) copper-based alloys: bronze coinage in Magna Graecia and Rome (5th to 2nd centuries BCE). (September 2020) - Westner, Katrin J.; Kemmers, Fleur; Klein, Sabine
Abstract: Lead is a ubiquitous and ambiguous component of ancient copper-based artefacts as it can be a residue of the ore or could have been deliberately added. In this study, we present compositional and Pb isotope data of a set of Roman, Syracusan and south Italian indigenous bronze coins from the 5th to 2nd centuries BCE. We describe an approach that considers the Pb content and its potential implications for provenance and technology as a variable alongside Pb isotope source characteristics. By combining elemental with isotopic data of lead and, in a subsequent step, with trace element signatures, this method allows to identify endmembers of natural and/or anthropogenic mixing and to outline their possible provenance. In a wider context, our results show how the existing bronze currencies transform parallel to the changing political situation and how Rome's bronze monetary instruments develop from a combination of local tradition and Greek practices into a coinage in its own right. Highlights: Novel combined approach for elemental and Pb isotope data of (leaded) copper alloys. Method is independent of threshold values for lead debasement and literature reference data. Evolution of bronze coinages of southern Italy and Sicily and transformation of Rome's bronze currency into a coinage in its own right.